The Effect of Light Wavelength on Water Quality in Photocatalytic Seawater Pre-treatment - Weerana, Eh Kan; Ruzinah, Isha (Universiti Malaysia Pahang, 2016)
Alternative pre-treatment of seawater via photocatalytic reaction is not well explored. Although titanium oxide (TiO2) is widely used in photocatalytic reaction, the application of other material especially from biomass ash is rare. In this research, the effect of light wavelength for seawater treatment and the degradation of organic pollutants by using hybrid TiO2 photocatalyst supported by oil palm fiber ash (biomass ash) are studied. The photocatalyst which consisted of TiO2 and oil palm fiber ash weight ratio of 1:1 (i.e Ti:Ash 50:50) was synthesized via wet impregnation method. The Ti:Ash 50:50 photocatalyst was calcined at 500°C in the presence of air. The experiment was performed in a one litre borosilicate photocatalytic reactor. The percentage weight ratio of 1:400 for catalyst to seawater sample was set. The mixture of photocatalyst and water sample was stirred at 400 rpm to have homogenized distribution of the photocatalyst in the water. The investigation was carried out for two hours by exposing the reactor with either 365 nm or 420 nm mercury light. The photocatalyst was characterized by using N2 adsorption (BET) and UV/Vis/Nir to determine the specific surface area, pore volume and pore size and band gap energy of the catalyst respectively. The Ti:Ash 50:50 band gap energy was obtained at 3.1eV. This indicates that the catalyst was reactive when less than 385 nm light wavelength was used. The quality of initial and product seawater was analyzed via pH, conductivity, turbidity and chemical oxygen demand (COD). The small reduction of conductivity and COD obtained when using Ti:Ash 50:50 without light present shows the system was dominant by adsorption without no reaction. Higher reduction of conductivity, pH, turbidity and COD was achieved when the Ti:Ash 50:50 photocatalyst was exposed to 365 nm light wavelength than the Ti:Ash 50:50 photocatalyst that was exposed to 420 nm light wavelength. In addition, significant increment of water temperature (from 25°C to 100°C) was observed when 420 nm light wavelength was used. This leads to distillation dominated the process rather than photocatalytic reaction. It can be deduced that hybrid photocatalyst of Ti:Ash 50:50 has remarkable capabilities in pre-treatment and purify the seawater. The light wavelength also plays important role in adsorption behavior and photocatalytic activity of the catalyst.